2019
DOI: 10.1038/s41598-018-36511-z
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Levels, Biological Enrichment Capacities and Potential Health Risk Assessment of Trace Elements in Eichhornia crassipes from Honghu Lake, China

Abstract: This study investigated the concentrations of Zn, Cu, Cr, Pb, As and Cd in different tissues of E . crassipes from Honghu Lake. The total concentrations of trace elements in E . crassipes were observed in descending order: Zn (111.6162) > Cu (15.7494) > Cr (7.0466) > Pb (5.6251) > As (3.6831) > Cd (0.1941) mg/kg. The order of the bioconcentration factor (BCF) measured in E . crassipes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…CSF is the oral carcinogenic slope factor of carcinogenic metals (kg d)/mg. CSFs for Cr, Cd, Pb, and As are 0.5, 0.38, 0.0085, and 1.5 (kg d)/mg, respectively ( Lim et al, 2018 ; Zhang et al, 2019 ). In general, the acceptable CRi standard ranges from 10 −6 to 10 −4 ( USEPA, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…CSF is the oral carcinogenic slope factor of carcinogenic metals (kg d)/mg. CSFs for Cr, Cd, Pb, and As are 0.5, 0.38, 0.0085, and 1.5 (kg d)/mg, respectively ( Lim et al, 2018 ; Zhang et al, 2019 ). In general, the acceptable CRi standard ranges from 10 −6 to 10 −4 ( USEPA, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a triangular fuzzy number was used to handle the ambiguity of the difference coefficient. Combining the weights of each indicator, a coupling model with a combination of TFN and SPA was established [67][68][69], as shown in Equations (5) and (6).…”
Section: The Comprehensive Evaluation Model Of Spa and Triangular Fuzmentioning
confidence: 99%
“…Water is the basic natural resource for human beings and all living things to survive and develop [4]. With the rapid development of the social economy, water resources are over-committed [5][6][7], as well as the massive discharge of industrial, agriculture, and domestic sewage, due to the poor management of water resources, leading to a reduction in water quantity and the decline in water quality [8][9][10]. Great attention should be paid to the problem of water distance from east to west is 132.1 km, and the maximum distance from north to south is 154.0 km.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the aggravation of environmental pollution and the influence of some natural factors, some heavy metals widely existing in the surrounding environment will also enter people's lives with the use of cosmetic raw materials (9)(10)(11). Studies have shown that low-dose but long-term exposure of heavy metals to the human body can cause chronic poisoning or even canceration, causing irreversible adverse effects on human organs and seriously threatening human health (12)(13)(14). As one of the most commonly used cosmetics for modern women, lip cosmetics can not only moisten the lips but also improve personal performance (15).…”
Section: Introductionmentioning
confidence: 99%